2004
DOI: 10.1186/ar1336
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction The Bone and Joint Monitor Project was developed to quantify the global burden of musculoskeletal conditions and develop strategies for their prevention. Experts within the Monitor Project have worked previously with officers at the World Health Organization (WHO) to estimate morbidity and mortality associated with rheumatic conditions. The present collaboration seeks means of providing additional and more current burden data. Objective To develop recommendations for performing epidemiological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on multiple genome scans, chromosomes 2, 4, 7, 11 and 16 are now considered as the most likely candidates. Finer linkage analysis narrowed the locus on chromosome 2 to 2q24.3-q31.1, a region which contained 85 known genes [124], but none of these were cartilage-related genes. Other studies suggested that major susceptibility loci were unlikely to be present in this region of 2q [114,125].…”
Section: Genetics Of Osteoarthritismentioning
confidence: 99%
“…Based on multiple genome scans, chromosomes 2, 4, 7, 11 and 16 are now considered as the most likely candidates. Finer linkage analysis narrowed the locus on chromosome 2 to 2q24.3-q31.1, a region which contained 85 known genes [124], but none of these were cartilage-related genes. Other studies suggested that major susceptibility loci were unlikely to be present in this region of 2q [114,125].…”
Section: Genetics Of Osteoarthritismentioning
confidence: 99%
“…The missense mutation frequency is slightly greater than 2% in patients in the Icelandic population (15). FRZB (2q32.1), which encodes both the chondrogenic regulator secreted frizzled-related protein 3, and CILP (15q22.31) that codes for a cartilage intermediate-layer protein, has also been reported to be associated with OA in females (16,17).…”
Section: Compmentioning
confidence: 99%